Correlation between Microdilution, E-test, and Disk Diffusion Methods for Antifungal Susceptibility Testing of Posaconazole against Candida spp. - Sims, Charles R. (American Society for Microbiology, 2006)
Agar-based antifungal susceptibility testing is an attractive alternative to the microdilution method. We examined the correlation between the microdilution, E-test, and disk diffusion methods for posaconazole against Candida spp. A total of 270 bloodstream isolates of Candida spp. with a broad range of posaconazole MICs were tested using the CLSI M27-A2 method for microdilution, as well as the M-44A method and E-test methods for agar-based testing on Mueller-Hinton agar supplemented with 2% glucose and 0.5 μg of methylene blue. MICs and inhibitory zone diameters at the prominent growth reduction endpoint were recorded at 24 and 48 h. The Candida isolates included Candida albicans (n = 124), C. parapsilosis (n = 44), C. tropicalis (n = 41), C. glabrata (n = 36), C. krusei (n = 20), C. lusitaniae (n = 3), and C. dubliniensis (n = 2). The overall concordance (i.e., the percentage of isolates within two dilutions) between the E-test and microdilution was 64.8% at 24 h and 82.6% at 48 h. When we considered an arbitrary breakpoint of ≤1 μg/ml, the agreement between the E-test and microdilution methods was 87.8% at 24 h and 93.0% at 48 h. The correlation of MICs with disk diffusion zone diameters was better for the E-test than the microdilution method. Zone correlation for diameters produced by the disks of two manufacturers was high, with a Pearson test value of 0.941 at 24 h. The E-test and microdilution MICs show good concordance and interpretative agreement. The disk diffusion zone diameters are highly reproducible and correlate well with both the E-test and the microdilution method, making agar-based methods a viable alternative to microdilution for posaconazole susceptibility testing.